Hagiotoponyms: A Special Case of Reflection of Mental Capacity in Geographical Names - Bugaeva, Irina (Respectus Philologicus, 2006)
This article is dedicated to the analysis of the sacred toponyrnics as a means of expression of religious world-view. The definitions of mentality and mental capacity remain speculative. However, one important component is absent in all available interpretations. That is the religious component. In the article, the correlation of hagiotoponyms and sacred toponyms is examined, and illustrated by examples from literature and spoken language.  Specifications of defining the terms hagionym. hagiotoponym. hagioanthroponym are provided; for the first time the definition of festonym as a term is given, which describes celebrations in the structure of onomastics. The author comes to the conclusion that the sacred toponyrnics are made by hagiotoponyms going down to theonyms and hagioanthroponyms in their origin, as well as precedent toponyms containing a religious semantic part in their structure. All toponyms going under the category of sacred toponymics have a lexical background, i. e. knowledge which is necessary for adequate understanding of religious texts.